Characteristic of the contracts - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article deals with different approaches to the content of the term «types of agreement». Also the authornotices the necessity to delimit such concepts: where are the types of agreement, and where their descriptionsare. The author proves the inadmissibility of substitution of the categories and offers his own vision of the characteristics of contracts in civil law based on the dichotomy. It is also introduces an additional, previously unknown to the science of civil law, criterion for contracts’ classification – capacity to renew, also proposes to allocate renewable and nonrenewable contracts.